Minds without fear philosophy in the Indian renaissance - Bhushan, Nalini; Garfield, Jay L. 1955- (Oxford University Press, 2017)
This is an intellectual and cultural history of India during the period of British occupation. It demonstrates that this was a period of renaissance in India in which philosophy - both in the public sphere and in the Indian universities - played a central role in the emergence of a distinctively Indian modernity
Previously issued in print: 2017
Keywords: Geschichte 1800-1960; Philosophy, Indic / History; Indische Philosophie; India / Intellectual life